2016
DOI: 10.1186/s12906-016-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization and antioxidant and antiproliferative activities of the aqueous extracellular polysaccharides from the thermophilic microalgae Graesiella sp.

Abstract: BackgroundFor thousands of years, Tunisian geothermal water has been used in bathing. Indeed, thermal baths “Hammam” were recommended in the treatment of different type of illnesses as, for instance, for relaxing joints and soothing. The ability of microalgae to sustain at the high temperature makes them potential producers of high value thermostable bio-products. This study aimed to explore the therapeutic potential of the aqueous extracellular polysaccharides (AEPS) of the Tunisian thermophilic microalgae Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…on ferrous ion-chelating ability was 0.33 mg/mL (stronger than EDTA), and on hydroxyl radical scavenging was 0.87 mg/mL (ascorbic acid was 1.1 mg/mL) ( Table 1). The strong antioxidant activity may be related to its structure, high uronic acid (24%) and high protein (12%) ( Table 1) [51]. Furthermore, the in vivo antioxidant effects of microalgal EPS need to be further studied.…”
Section: Microalgal Polysaccharidesmentioning
confidence: 99%
“…on ferrous ion-chelating ability was 0.33 mg/mL (stronger than EDTA), and on hydroxyl radical scavenging was 0.87 mg/mL (ascorbic acid was 1.1 mg/mL) ( Table 1). The strong antioxidant activity may be related to its structure, high uronic acid (24%) and high protein (12%) ( Table 1) [51]. Furthermore, the in vivo antioxidant effects of microalgal EPS need to be further studied.…”
Section: Microalgal Polysaccharidesmentioning
confidence: 99%
“…They can be used as thickeners, emulsifying agents and biosurfactants, with applications in the food and biomedical industry. Antibacterial (Mundt et al 2001), antioxidant (Trabelsi et al 2016) and anti-in ammatory properties (Xiao et al 2018) have already been reported for EPS of cyanobacteria.…”
Section: Introductionmentioning
confidence: 86%
“…They can either be loosely attached to the cell wall or excreted into the environment [27,28]. Many microalgae, especially a variety of red algae and cyanobacteria, are producers of structurally diverse EPS.…”
Section: Exopolysaccharides (Eps)mentioning
confidence: 99%